40. POST-MORTEM NEUROPATHOLOGIC FINDINGS IN UNVERRICHT-LUNDBORG DISEASE (PROGRESSIVE MYOCLONIC EPILEPSY TYPE I): A CASE REPORT. (February 2015) - Merrick, Kathleen; Sy, Joanne; Reddel, Stephen
Abstract : Unverricht-Lundborg disease (ULD) is the most common seizure disorder in the rare subgroup of progressive myoclonic epilepsies. Patients typically present between the ages of 6 and 16 with onset of stimulus and/or photosensitive myoclonus as well as generalised tonic-clonic seizures. Progressive cerebellar degeneration leads to the development of ataxia, incoordination, dysarthria and intention tremor. ULD is typified by specific mutations in the CSTB gene located at chromosome 21q22.3. While the clinical features and genetic abnormalities of this disease are well known, detailed neuropathological examination is rarely described in the published literature. We present the neuropathological findings of a genetically verified case of Unverricht-Lundborg disease in a 74 year old female. The deceased had a history of recurrent seizures and presented to hospital after an episode of status epilepticus. She subsequently passed away after presumed aspiration. At autopsy, macroscopic examination of the brain revealed mild frontotemporoparietal atrophy. The cerebellum showed marked atrophy, particularly inferiorly and dorsally. Microscopic examination of the hippocampus was unremarkable, and in particular there was no evidence of hippocampal sclerosis. Marked cerebellar atrophy was confirmed microscopically affecting the cerebellar cortex and subjacent white matter. Incidental cerebellar heterotopias were also noted.